Persepsi dan Preferensi Kalangan Ibu terhadap Kampanye Aqua #BijakBerplastik di Instagram - Kayla Cahya Kinasih; Fadila Hafsyah Aprilia; Fadillah Putri Safira; Naila Diva Azalia; Rizky Ramadhani Putri Brando (CV. ITTC INDONESIA, 2026)
The increasing volume of household plastic waste in urban areas has become an increasingly complex environmental problem due to the low level of public awareness in managing plastic waste in daily life. In response to this issue, environmental campaigns through social media, such as Aqua’s #BijakBerplastik campaigns on Instagram, have emerged as an effort to raise public awareness of plastic waste reduction, particularly among mothers who play an important role in managing household consumption. Based on this context, this study aims to understand the perceptions and content preferences of Generation Y mothers in the Greater Jakarta area (Jabodetabek) toward Aqua’s #BijakBerplastik campaign on Instagram, as well as how they interpret the campaign messages in their daily lives. To achieve this objective, this study employed a qualitative descriptive method using in-depth interviews with four Generation Y mothers who have different educational backgrounds, occupations, and social media usage habits. The findings indicate that the campaign was positively received because it was considered relevant to mothers’ roles in managing household needs and plastic waste. Positive perceptions were reinforced by the informants’ personal experiences related to environmental conditions in their residential areas, which are vulnerable to waste and flooding issues. Campaign exposure occurred organically through Instagram’s algorithm, while content preferences were influenced by visual appeal, narrative flow, and clarity of technical information. The campaign was perceived as effective when it presented practical and applicable examples of real actions in daily life.